Motif-Motif Tenun Pandaisikek sebagai Interpretasi Falsafah Alam Takambang Jadi Guru - Jonson Handrian Ginting (Universitas Andalas, 2013)
Minangkabau people have ability to interpretate nature for Pandaisikek woven patterns and motifs. Furthermore this situation encourages weaving pattern to match what is in the culture so interpretated symbolically on the woven motifs. In other words, the symbols on the woven motifs have meanings that refer to the idea of the shape and behavior of the philosophical idealism. This article describes some of the Pandaisikek woven motifs. The woven motifs are people interpretation of nature as one of the symbols and learning materials to the next generation.